The Suzuki−Miyaura Cross-Coupling−Claisen Rearrangement−Cross-Metathesis Approach to Prenylated Isoflavones - George, Kwesiga; Julia, Greese; Alexandra, Kelling; Eric, Sperlich; Bernd, Schmidt (American Chemical Society, 2023)
Isoflavones were synthesized via Suzuki−Miyaura coupling of 3-iodochromones and para-methoxybenzene- and para- phenolboronic acid. In our hands, conditions commonly used for similar cross couplings turned out to be unsuccessful or difficult to reproduce, for example, due to the unplanned partial cleavage of MOM-protecting groups. Using Pd(dba)2 as a precatalyst and tricyclohexylphosphine as an activating ligand, reliable cross-coupling conditions were identified. In all cases, notably higher yields of isoflavones were obtained with para-phenolboronic acid than with para-methoxybenzene boronic acid. This observation and the commercial availability of para-phenolboronic acid suggest that for the synthesis of the important 3′-prenyl- or 3′,5′-diprenylisoflavone substitution pattern a synthetic route that introduces the prenyl substituents after the Pd-catalyzed cross-coupling step, thereby avoiding laborious and protecting-group-intensive multistep syntheses of C-prenylated arene boronic acids, is advantageous